Climate-Smart Agriculture and Trade-Offs With Biodiversity and Crop Yield - Tripathi, Hemant G.; Kunin, William E.; Smith, Harriet E.; Sallu, Susannah Mary; Maurice, Sixbert; Machera, Suzan D.; Davies, Rhiannon; Florence, Mosha; Eze, Samuel; Yamdeu, J. H. Galani; Sait, Steven Mark (Frontiers in Sustainable Food Systems, 2022)
Biophysical evaluations of climate-smart agriculture (CSA) often overlook the potential interactions with and implications for biodiversity and ecosystem services, which are important determinants of food system resilience and sustainability. Drawing on a case study in the East Usambara Mountains, Tanzania, we compare the impacts of CSA with other agricultural management practices on invertebrate pest and natural enemy diversity, and the associated effects on crop damage and crop yield. We found that the most common CSA practices in the region, terracing and trenching with live and compost mulches, provided the best outcomes for crop production, pest suppression and agricultural income. However, greater diversity of pests was observed when neighbouring fields planted improved crop varieties suggesting that the use of improved varieties by farmers is creating increased vulnerability to pest damage among neighbouring farmers that used local varieties. Also, greater natural enemy diversity was found when neighbouring fields were either intercropped or left fallow highlighting spatial flows of ecosystem services between fields. Landcover heterogeneity was positively correlated with pest diversity, whilst landcover richness was positively associated with higher pest volume, highlighting the importance of landscape characteristics in pest and natural enemy dynamics. Finally, we found that crop damage was most severe when pest communities had low species richness, suggesting that a small number of key crop pests contribute to most yield losses. Our findings illustrate that varied combinations of agricultural management practices lead to heterogeneous biodiversity outcomes and trade-offs, and highlight the importance of local management, neighbourhood effects and landscape characteristics. CSA evaluations must therefore look beyond productivity as a measure for success, as trade-offs with invertebrate biodiversity, food production, and environmental sustainability often interact and feedback in complex and unexpected ways.